Giardia Detection and Codetection With Other Enteric Pathogens in Young Children in the Vaccine Impact on Diarrhea in Africa (VIDA) Case-Control Study: 2015–2018. (19th April 2023) - Marcenac, Perrine; Traoré, Awa; Kim, Sunkyung; Prentice-Mott, Graeme; Berendes, David M; Powell, Helen; Kasumba, Irene N; Nasrin, Dilruba; Jones, Joquina Chiquita M; Zaman, Syed M A; Ochieng, John B; Juma, Jane; et al.
Abstract: Background: Giardia has been associated with reduced risk of diarrhea in children in low-resource settings, but the mechanism underlying this association is unknown. To assess whether Giardia may shape colonization or infection with other enteric pathogens and impact associations with diarrhea, we examined Giardia and enteric pathogen codetection among children <5 years old in Kenya, The Gambia, and Mali as part of the Vaccine Impact on Diarrhea in Africa study. Methods: We tested for Giardia and other enteric pathogens using enzyme-linked immunosorbent assays and real-time polymerase chain reaction (PCR) on stool, respectively. We evaluated associations between Giardia and enteric pathogen detection using multivariable logistic regression models separately for children with moderate-to-severe diarrhea (MSD, cases) and free of diarrhea (controls). Results: Among 11 039 enrolled children, Giardia detection was more common among controls (35%) than cases (28%, P < .001). Campylobacter coli/jejuni detection was associated with Giardia in controls in The Gambia (adjusted odds ratio [aOR] [95% confidence interval CI]: 1.51 [1.22‒1.86]) and cases across all sites (1.16 [1.00‒1.33]). Among controls, the odds of astrovirus (1.43 [1.05‒1.93]) and Cryptosporidium spp. (1.24 [1.06‒1.46]) detection were higher among children with Giardia . Among cases, the odds of rotavirus detection were lower in children with Giardia in Mali (.45 [.30‒.66]) and Kenya (.31 [.17‒.56]). Conclusions: Giardia was prevalent in children <5 years old and was associated with detection of other enteric pathogens, with differing associations in cases versus controls and by site. Giardia may affect colonization or infection by certain enteric pathogens associated with MSD, suggesting an indirect mechanism of clinical impact. Abstract : Giardia was prevalent in children <5 years old and was associated with detection of other enteric pathogens, including rotavirus. Giardia may affect colonization or infection by certain enteric pathogens associated with MSD, suggesting an indirect mechanism of clinical impact.